Hakikat Kerja Sama Dalam Pemgembangan Manajemen Pendidikan Islam - Setiabudi, Agung (MADINAH, 2021)
Education is very important in all aspects of life, both formal, non-formal and informal. Therefore, high-quality education is needed to develop quality human beings. Unfortunately, the current state of education shows the opposite. Curriculum mismatches, scarcity of high-quality resources, inadequate infrastructure, low levels of attainment, and lack of coordination among stakeholders all hinder problems that hinder the improvement of the quality of education. It requires the direct participation and cooperation of all stakeholders to achieve the common goal of improving the quality of education. In other words, genuine collaboration is needed to ensure that no function overlaps with another. Government, community, and schools are stakeholders in the world of education. What is meant by "community" is parents and the surrounding environment. While school is used to refer to students, lecturers, and administrators. This presentation will explore the critical nature of collaboration among all stakeholders to improve the quality of education.